Gel-assisted crystallization of [Ir4(IMe)7(CO)H10]2+ and [Ir4(IMe)8H9]3+ clusters derived from catalytic glycerol dehydrogenation. Issue 42 (5th October 2015) - Sharninghausen, Liam S.; Mercado, Brandon Q.; Crabtree, Robert H.; Balcells, David; Campos, Jesús
Abstract : Two unique Ir4 clusters isolated during catalytic glycerol dehydrogenation, crystallized using aqueous and organic gel matrices and displaying remarkable structural features are described. Abstract : The two title clusters were formed during iridium-catalyzed glycerol dehydrogenation and display a remarkably high NHC content. They were crystallized in either agarose or polyethylene oxide gel matrices, while more conventional crystallization techniques proved unsuccessful. Cluster [Ir4 (IMe)8 H9 ] 3+, with a net charge of +3, was only crystallizable with a polyoxometalate Keggin trianion. The crystal packing of this intercluster compound is discussed. Computational studies position the iridium hydrides and provide insights into the bonding.